Pemanfaatan Media Sosial Humas Polda Riau Dalam Memberikan Informasi Kepada Publik - Afifah Ramlah; Welly Wirman (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Social Media has enabled the birth of new forms of social and social organizations and then transformed into a "new weapon" for organizations or institutions in disseminating messages and information to their communities, including the police. This can be seen in the social planning media used by the Riau Regional Police Public Relations (Polda Riau Public Relations). Social media planning for Instagram and Facebook is prioritized for the latest publications and information related to information about the police. This research uses qualitative research methods and analysis with the concept of The Circular Model of SOME. The subject of this research is social media communication planning on the Riau Regional Police Public Relations media. Data collection was carried out through documentation studies, observations and interviews. Data analysis techniques by reducing data, presenting data, and drawing conclusions. Apart from that, data validity checking techniques use triangulation of sources and methods. The results of this research show that it is possible to utilize technological developments in the field of social media to disseminate information related to police activities themselves. The ease of conveying Riau Regional Police Public Relations information between the community and the police makes it easier to carry out their public relations duties. Therefore, it is necessary to use social media optimally in the Riau Regional Police's Public Relations duties in providing information services for Riau regional police activities. This is supported by using the SoMe concept.